2022
DOI: 10.1113/ep089917
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic cardiac adaptations in adults born preterm

Abstract: New Findings What is the topic of this review?Studies using cardiovascular magnetic resonance imaging and echocardiography to investigate cardiac alterations at rest and during exercise‐induced physiological stress in adults born preterm. What advances does it highlight?People born preterm have a greater long‐term cardiovascular risk, which may be explained in part by their cardiac structural and functional alterations. They have potentially adverse alterations in left and right ventricular structure and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Experimental animal and human preterm birth studies have found evidence of cardiac remodeling that result in increased biventricular mass, smaller ventricular cavities and volumes, and altered cardiac shape (more spherical than elliptical; Tan & Lewandowski, 2020). These anatomical remodeling changes influence ventricular function, causing lower ejection fraction, stroke volume, and cardiac output (Lewandowski, 2022). These changes have also been found to persist beyond childhood, predisposing those born prematurely to an increased risk of CVD conditions like hypertension, heart failure, and coronary artery disease as young adults (Crump, et al, 2021;Crump, 2020;Lewandowski, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental animal and human preterm birth studies have found evidence of cardiac remodeling that result in increased biventricular mass, smaller ventricular cavities and volumes, and altered cardiac shape (more spherical than elliptical; Tan & Lewandowski, 2020). These anatomical remodeling changes influence ventricular function, causing lower ejection fraction, stroke volume, and cardiac output (Lewandowski, 2022). These changes have also been found to persist beyond childhood, predisposing those born prematurely to an increased risk of CVD conditions like hypertension, heart failure, and coronary artery disease as young adults (Crump, et al, 2021;Crump, 2020;Lewandowski, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…These anatomical remodeling changes influence ventricular function, causing lower ejection fraction, stroke volume, and cardiac output (Lewandowski, 2022). These changes have also been found to persist beyond childhood, predisposing those born prematurely to an increased risk of CVD conditions like hypertension, heart failure, and coronary artery disease as young adults (Crump, et al, 2021;Crump, 2020;Lewandowski, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Christopher Stewart and colleagues discuss the wonders of the human gut microbiome and its role in regulating physiology throughout the lifecourse (Ahearn-Ford et al, 2022). The post-natal period up to 3 years of age is especially important in setting the parameters of homeostasis and maturation as microbes colonize the human Adam Lewandowski also considers the impact of PTB on physiological outcomes later in life (Lewandowski, 2022). PTB, as mentioned above, is a risk factor for later development of cardiovascular disease.…”
mentioning
confidence: 99%
“…These intricate studies provide valuable information as to the possible mechanisms contributing to the increased cardiac disease risk of being born prematurely. Of interest is a cross‐over of potential benefits remarked upon in the reviews of Lewandowski (2022) and Ahearn‐Ford et al. (2022) – for cardiac performance or gut microbiome homeostasis respectively – of continuous breast‐feeding of preterm infants.…”
mentioning
confidence: 99%
See 1 more Smart Citation